Real-World Data on Health-Related Quality of Life Assessment in Patients With Breast Cancer Receiving Subcutaneous Trastuzumab. (16th February 2018) - Syrios, John; Pappa, Evelina; Volakakis, Nikolaos; Grivas, Anastasios; Alafis, John; Manioudaki, Sofia; Tzouda, Vasiliki; Korogiannos, Athanasios; Rapti, Cleopatra; Koufopoulos, Nektarios; Nikolaidou, Adamantia; Kanavou, Eleftheria; et al.
Purpose: Trastuzumab, a humanized anti-human epidermal growth factor receptor 2 (anti-HER2) antibody delivered intravenously, has revolutionized the treatment of patients with breast cancer overexpressing HER2 protein. Recently, a newer subcutaneous formulation was shown to have comparable efficacy to the initial intravenous trastuzumab. In this study, we aimed to evaluate the impact of subcutaneous trastuzumab on the health-related quality of life (HRQoL) of patients diagnosed with early or metastatic HER2-overexpressing breast cancer. Methods: Patients were provided with the EORTC QLQ-C30 (European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire-Core 30) and the BR-23 questionnaires. The scoring of questionnaires and patient's sociodemographic and clinicopathologic characteristics were recorded and analyzed by descriptive and correlation statistics employing t test and 2-way analysis of variance. Results: A total of 163 patients agreed to participate in the study. About 90 of 163 patients (55.21%) received subcutaneous trastuzumab and 21 patients intravenous trastuzumab (12.88%). A control group of 52 HER2+ patients received chemotherapy without trastuzumab (31.90%). Patients receiving subcutaneous trastuzumab were older and of more advanced disease stage compared with those receiving chemotherapy (58.5 vs 51 years, 39.8% vs 28.8% advanced disease). In univariate analysis, subcutaneous trastuzumab was associated with less nausea and vomiting ( P = .002) but worse cognitive function ( P = .013) and dyspnea ( P = .042). Patients who have received >8 cycles of subcutaneous trastuzumab reported less diarrhea ( P = .049) and systemic therapy side effects ( P = .015). Multivariate analysis showed that patients without comorbidity receiving subcutaneous trastuzumab had less treatment side effects, less upset by hair loss, and higher emotional functioning. Of note, mastectomy and subcutaneous trastuzumab were associated with improved role functioning ( P = .021). In metastatic disease, no negative impact of subcutaneous trastuzumab on HRQoL was found. Conclusions: The administration of subcutaneous trastuzumab improved certain symptoms and did not adversely affect most of the assessed functional scales. Particularly, in the metastatic setting, subcutaneous trastuzumab had no negative impact on HRQoL.